THE USE OF BIOLOGICAL PRODUCTS IN ABDOMINAL SURGERY AND LIVER TRANSPLANTATION - N. I. Gabrielyan; L. I. Arefieva; E. M. Gorskaya; M. N. Kornilov; Y. G. Moysyuk; O. M. Tsirulnikova (Вестник трансплантологии и искусственных органов, 2013)
This article provides an overview of new approaches to the prevention of infectious complications of bacterial nature after the high-technology operations in the abdominal surgery, first of all, after liver transplantation. At- tention is drawn to the first positive results of randomized studies on the use of biological preparations - probi- otics, prebiotics and synbiotics in patients after liver transplantation. The authors prove the prospects of further development of this subject based on successful model experiments on animals and various operational interven- tions in abdominal surgery.